Efektivitas Penggunaan Dana Desa terhadap Pengembangan Infrastruktur Desa dan Pengembangan Potensi Ekonomi Lokal di Kecamatan Tambun Utara Kabupaten Bekasi: Studi Kasus Desa Karang Satria - Najmuddin, Najmuddin; Achmad, Mansyur; Suwanda, Dadang (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
To overcome problems in village development, the government provides village funds. The form of use can be in the form of village infrastructure development and development of local economic potential. The aim of this research is to obtain an overview and describe the effectiveness of the use of village funds for village infrastructure and the development of local economic potential in North Tambun District, Bekasi Regency. The research methodology uses qualitative research with an inductive approach. Researchers want to know clearly about the effectiveness of the use of village funds in developing village infrastructure and developing local economic potential in Tambun Utara District, Bekasi Regency, especially in Karang Satria Village. The researcher describes the state of the research object and then discusses it to obtain general conclusions and understanding of the object under study. The results of this research are that the use of village funds for village infrastructure and local economic development in North Tambun District, especially in Karang Satria Village, was implemented effectively. The community gave positive responses and felt the benefits of the various programs that had been held, such as paving roads, providing public facilities, creating a drainage system, as well as adding facilities and infrastructure or office furniture. Providing village funds through BUM Des Satria Istiqomah has also provided benefits to the people of Karang Satria Village and its surroundings. BUM Des Satria Istiqomah has a permanent building and various economic improvement programs as well as business units that provide the best service for residents. In addition, there is the role of Mikro, Small, and Medium Enterprises (MSME) and MSMEs at the sub-district level which oversees various micro, small and medium enterprises. Through MSMEs, mutually beneficial reciprocal relationships are created between entrepreneurs, village governments, and village residents.